2015
DOI: 10.1021/cs501846g
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in Operando Studies in Heterogeneous Catalysis: Atomic and Electronic Structural Features in the Hydrogenation of Ethylene over Supported Pd and Pt Catalysts

Abstract: There exists an emerging opportunity, engendered by advances made in experimental methods of research, to address long-standing questions about the nature of the molecular mechanisms that are operative in important heterogeneous catalytic processes, as well as the nature of the complex atomic and electronic structural features that mediate them. Of particular interest in this regard is the understanding of the dynamical attributes of catalytic processesan understanding that might allow design principles to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 113 publications
1
40
0
Order By: Relevance
“…The assignation of weaker peak is too long to be ascribed Pt-O bonds from PtO2 (1.65 Å, see Figure S12), but according to literature data it is compatible with Pt-O bonds between Pt and the zeolite frameworks. 27 The presence of Pt-O bonds in Pt@MCM-22 sample has also been confirmed by the XANES spectrum of Pt@MCM-22. As it can be seen in Figure 3b, the curve shape of Pt@MCM-22 sample looks like Pt(0) (fist derivative and oscillations around 11580 and 11595 eV) but white line intensity is higher, indicating the presence of Pt-O bonds.…”
Section: Spectroscopic Characterization Of Samplesmentioning
confidence: 64%
“…The assignation of weaker peak is too long to be ascribed Pt-O bonds from PtO2 (1.65 Å, see Figure S12), but according to literature data it is compatible with Pt-O bonds between Pt and the zeolite frameworks. 27 The presence of Pt-O bonds in Pt@MCM-22 sample has also been confirmed by the XANES spectrum of Pt@MCM-22. As it can be seen in Figure 3b, the curve shape of Pt@MCM-22 sample looks like Pt(0) (fist derivative and oscillations around 11580 and 11595 eV) but white line intensity is higher, indicating the presence of Pt-O bonds.…”
Section: Spectroscopic Characterization Of Samplesmentioning
confidence: 64%
“…Determination of intrinsic reaction kinetics of catalyzed reactions is of importance in the safe and economical design and control of industrial chemical and environmental processes, and in the development of new and improved catalysts . Echoing all the assertions in this review, operando studies have shown that catalysts may undergo dynamic structural transformations upon small changes in the reaction conditions and such transformations have a strong impact on the performance of the catalysts . Strictly speaking, the active state of a catalyst only exists during the catalysis.…”
Section: Experimental Detection Of Metastable States In Catalysismentioning
confidence: 93%
“…[123][124][125][126][127][128] Echoing all the assertions in this review, operando studies have shown that catalysts may undergo dynamic structural transformations upon small changes in the reaction conditions and such transformations have a strong impact on the performance of the catalysts. 129,130 Strictly speaking, the active state of a catalyst only exists during the catalysis. Many crucial mechanistic questions remain poorly understood thanks to the inherent multiscale complexity of heterogeneous catalytic transformations.…”
Section: Experimental Detection Of Metastable States In Catalysismentioning
confidence: 99%
“…The work specifically investigates the active structures of silica-supported Pt clusters mediating the process of ethylene hydrogenation. Previous studies by operando XAFS have uncovered irreversible structural transformations in this system when it is cycled between hydrogen- and ethylene-rich environments 20 . Ex situ scanning transmission electron microscopy (STEM) studies showed that the average particle size is approximately the same after the reaction, but the measured variation was much smaller than the precipitous drop in the metal-metal coordination number measured by operando extended XAFS (EXAFS) 20 .…”
mentioning
confidence: 88%